Relation of body fat distribution to femoral neck bone density and endometrial thickness in postmenopausal women - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2010)
Study design. Subjects were 40 healthy postmenopausal women with biopsy proven atrophic endometrium. Anthropometrical variables (total fat mass, trunk and leg fat masses, lean body mass and femoral neck BMD) were measured by dual energy X-ray absorptiometry. Results. Femoral neck BMD was positively correlated with body mass index, total fat mass, trunk fat mass, leg fat mass and endometrial thickness, and negatively correlated with age, years since menopause and FSH levels. Trunk fat and age remained significant determinants of femoral neck BMD (R<SU2</SU = 32.9 %, p < 0.001) and endometrial thickness was significantly associated with femoral neck BMD and oestradiol levels (R<SU2</SU = 46.5%, p < 0.0001) on regression analysis. Conclusion. Truncal adiposity rather than overall adiposity or lean mass are more closely associated with femoral neck BMD and there is no relationship between subcutaneous fat mass and endometrial thickness in postmenopausal women.
Keywords: ADIPOSE-TISSUE DISTRIBUTION; MINERAL DENSITY; REPLACEMENT THERAPY; ELDERLY-WOMEN; SEX-HORMONES; CANCER-RISK; OLDER WOMEN; VITAMIN-D; MASS; MEN